2019
DOI: 10.1111/jace.16465
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of porosity, crack density, and CMAS penetration in thermal barrier coatings subjected to burner rig testing

Abstract: Degradation of thermal barrier coatings (TBCs) in gas‐turbine engines due to calcium–magnesium–aluminosilicate (CMAS) glassy deposits from various sources has been a persistent issue since many years. In this study, state of the art electron microscopy was correlated with X‐ray refraction techniques to elucidate the intrusion of CMAS into the porous structure of atmospheric plasma sprayed (APS) TBCs and the formation and growth of cracks under thermal cycling in a burner rig. Results indicate that the sparse n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…5(d). Similar results were found in a recent study by Mack et al where the CMAS infiltration (also in gradient, albeit more cycles and exposed repeatedly until failure) was observed to attack the grain boundaries of the splats leading to the dissolution of the 7YSZ [25]. The size and the structure of these grain features are comparable to what was shown in by Krause et al both after thermally etching the as-sprayed coating and after CMAS attack [28,60].…”
Section: Invited Papersupporting
confidence: 90%
See 1 more Smart Citation
“…5(d). Similar results were found in a recent study by Mack et al where the CMAS infiltration (also in gradient, albeit more cycles and exposed repeatedly until failure) was observed to attack the grain boundaries of the splats leading to the dissolution of the 7YSZ [25]. The size and the structure of these grain features are comparable to what was shown in by Krause et al both after thermally etching the as-sprayed coating and after CMAS attack [28,60].…”
Section: Invited Papersupporting
confidence: 90%
“…In the case of 7YSZ TBCs, the interactions with molten CMAS have been extensively studied throughout the literature [22,23,24,25,26]. It is known that the specific interactions can vary somewhat based on CMAS composition.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that a lower infiltration depth would be measured for samples produced using the traditional coating processes, i.e., atmospheric plasma spray (APS) and electron-beam-physical vapor deposition (EB-PVD). Mack et al [28] investigated the correlation between the evolution of porosity and crack density to CMAS penetration of TBCs using SEM coupled with X-ray refraction techniques. Their study suggested that pore structure is usually instantly fully loaded by the CMAS melt and that a more significant penetration depth is observed for materials with larger pore radii [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of TGO results in the cracking of the top layer [50]. This phenomenon is more obvious for TBCs fabricated by APS [43,51,52] ( Figure 5). According to previous primary simulation work [53], we can also observe a similar phenomenon that the growth rate of TGO near the peak region is higher than that near the valley region.…”
Section: Tgomentioning
confidence: 98%
“…The effects of horizontal and vertical cracks on the stress around the TGO (Thermally Growth Oxide) layer during thermal cycling were studied. Dong et al [43] fabricated YSZ coatings by APS, finding that TGO with different thickness was prepared by controlling the isothermal oxidation time of the bond-coat. Thermal cycling tests were carried out for different thicknesses of TGO at 1150 • C, the duration of each cycle was 240 s. The results indicated that the YSZ coating has strong adhesive strength, and excellent thermal shock resistance.…”
Section: Apsmentioning
confidence: 99%